2005
DOI: 10.2202/1542-6580.1298
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Adiponitrile Hydrogenation Over Rhodium-Alumina Catalysts

Abstract: The catalytic hydrogenation of adiponitrile is generally carried out industrially at high temperature and pressure over Ni-Raney catalysts, which have the disadvantages of possessing low mechanical resistance and of being pyrophoric. In this work adiponitrile was hydrogenated in a three phase stirred slurry reactor using rhodium over alumina powder as a catalyst instead. Catalysts were prepared with a ion exchange technique by contacting 100 micron alumina powder with a solution of hydrate rhodium cloride for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Accordingly, we have assumed that LH kinetics describe the present system. A LH kinetics model has also been applied by others in the related case of adiponitrile hydrogenation 5. If the system is not limited by the diffusion of substrate to the catalyst surface, it is likely that the rate determining step is instead the surface reaction, a concept consistent with our data.…”
Section: Resultssupporting
confidence: 81%
“…Accordingly, we have assumed that LH kinetics describe the present system. A LH kinetics model has also been applied by others in the related case of adiponitrile hydrogenation 5. If the system is not limited by the diffusion of substrate to the catalyst surface, it is likely that the rate determining step is instead the surface reaction, a concept consistent with our data.…”
Section: Resultssupporting
confidence: 81%
“…This fixed-bed reactor suffers the probability of temperature runaway during reaction, thus calling for new types of three-phase reactors with improved temperature control (Di Felice et al, 2005;Hoffer et al, 2004). The successful operation of a magnetically stabilized fluidizedbed reactor for the hydrogenation of adiponitrile over amorphous nickel alloy catalysts, at 74 • C and 2.2 MPa, with an adiponitrile conversion of 98% and hexamethylenediamine selectivity of 66.5% (Chen, 2003), suggested that gas-liquid-solid (G-L-S) three-phase MSFB reactors could adequately control the operating temper- atures for petrochemical processes involving highly exothermic reactions.…”
Section: Introductionmentioning
confidence: 99%